Unlocking the Power of Data: An Introduction to Data Analysis in Healthcare - Shukla, Sameer (International Journal of Computer Sciences and Engineering, 2023)
Healthcare data [1] is becoming more complex and voluminous, which makes it difficult to extract valuable insights and improve healthcare services. Data analysis can help solve this challenge by providing a powerful solution. In this paper, the authors introduce the concept of data analysis in healthcare and explain its significance in enhancing patient outcomes, reducing healthcare costs, and improving the quality of care. The authors also discuss the different types of healthcare data, including electronic health records, claims data, medical imaging data, and patient-generated data, and explain the techniques used in data preprocessing, including data cleaning, transformation, and integration. Moreover, the authors describe the techniques used in exploratory data analysis (EDA), such as data visualization, summary statistics, and correlation analysis, which can help identify patterns and trends in healthcare data. They also explain the various predictive modeling techniques used in healthcare data analysis, including regression analysis, decision trees, and neural networks, which can be used for predicting patient outcomes and identifying risk factors. Additionally, the authors discuss the development of clinical decision support systems using data analysis, which can assist healthcare professionals in making informed decisions about patient care. The paper provides real-world examples of how data analysis has been used in healthcare, such as predicting hospital readmissions, identifying high-risk patients, and improving medication adherence. Finally, the authors discuss emerging trends in data analysis in healthcare, such as the use of artificial intelligence and machine learning, and their potential impact on healthcare. Overall, this paper highlights the importance of data analysis in healthcare and its potential to revolutionize the industry.